Use of the latest web technology in school website development - Zahri, Muhammad; Ananda, Stella Clara; Fadilasari, Ika Putri (Research in Education and Technology (REGY), 2023)
Students and teachers of SMK Negeri 1 Pontianak have achieved numerous academic and non-academic accomplishments, which, however, have not been documented and published on the school’s website portal. This research used a literature review method, studying various sources, including journals and the internet. The data used for this research had been collected and published in national online journals between the years 2017 and 2023. The researcher searched research journals published on the internet using Google Scholar, with a focus on full-text access. The abstract and full texts of the journals were carefully examined and analyzed. The research objectives and findings were extracted and analyzed using content analysis of the journals. The web-based school information system at SMK Negeri 1 Pontianak was developed to provide information and an overview of the school to the community, enabling them to familiarize themselves with the institution. The need for information related to both academic and non-academic aspects of students is also crucial for parents or guardians. The creation of a virtual tour using 360-degree photos is highly influenced by the choice of camera, selection of shooting spots, and photo stitching software. A 360-degree camera facilitates image capture compared to regular cameras, which merge to form panoramic photos. The Multimedia Virtual Tour 360 effectively describes the school’s location.